The influence of silicon on components of resistance to blast in susceptible, partially resistant, and resistant cultivars of rice - Seebold, KW; Kucharek, TA; Datnoff, LE; Correa Victoria, Fernando J.; Marchetti, MA (Scientific Societies, 2001)
The application of silicon (Si) fertilizers reduces the severity of blast, caused by Magnaporthe grisea, in irrigated and upland rice; however, little research has been conducted to examine the epidemiological and etiological components of this reduction. Four cultivars of rice with differential susceptibilities to race IB-49 of M. grisea were fertilized with three rates of a calcium silicate fertilizer and inoculated with the pathogen to test the effects of Si on the following components of resistance to blast: incubation period, latent period, infection efficiency, lesion size, rate of lesion expansion, sporulation per lesion, and diseased leaf area. For each cultivar, the incubation period was lengthened by increased rates of Si, and the numbers of sporulating lesions, lesion size, rate of lesion expansion, diseased leaf area, and number of spores per lesion were reduced. Lesion size and sporulation per lesion were lowered by 30 to 45%, and the number of sporulating lesions per leaf and diseased leaf area were significantly reduced at the highest rate of Si. The net effect of Si on these components of resistance is an overall reduction in the production of conidia on plants infected with M. grisea, thereby slowing the epidemic rate of blast.